Pedagogical Content Knowledge Analysis of Mathematics Teachers in Developing Lesson Plans on Ratio Topic - Ahmad Badawi; Tatang Herman; Dadang Juandi (Program Studi Tadris Matematika IAIN Salatiga, 2023)
In preparing a Lesson Plan, a mathematics teacher should pay attention to pedagogical principles, including general and mathematical pedagogy. Teacher knowledge related to these two pedagogies is called Pedagogical Content Knowledge (PCK). This study aims to analyze the PCK of a mathematics teacher at a junior high school in Kebumen when preparing lesson plans and carrying out learning activities on Ratio Topics. This study used a qualitative research method with a case study design. The teacher’s PCK analyzed in this study was divided into two parts: general pedagogical knowledge and mathematical pedagogical knowledge. The results showed teachers' general pedagogical knowledge when learning was more complete than when compiling lesson plans. Likewise, in mathematical pedagogy, the teacher's mathematical pedagogy knowledge when carrying out education is better than when compiling lesson plans. This also indicates a mismatch between the lesson plans compiled by the teacher and the learning activities he carried out. Therefore, in compiling lesson plans, teachers are advised to pour all pedagogical content knowledge that they have so that the lesson plans are by the learning activities carried out by the teacher so that the entire learning process can be carried out more optimally.